Superconvergence Error Estimates of the Lowest-Order Raviart-Thomas Galerkin Mixed Finite Element Method for Nonlinear Thermistor Equations (Journal of Computational Mathematics, 2025)
This paper is concerned with the superconvergence error estimates of a classical mixed finite element method for a nonlinear parabolic/elliptic coupled thermistor equations. The method is based on a popular combination of the lowest-order rectangular Raviart-Thomas mixed approximation for the electric potential/field $(φ,θ)$ and the bilinear Lagrange approximation for temperature $u$. In terms of the special properties of these elements above, the superclose error estimates with order $\mathcal{O}(h^2)$ are obtained firstly for all three com ponents in such a strongly coupled system. Subsequently, the global superconvergence error estimates with order $\mathcal{O}(h^2)$ are derived through a simple and effective interpolation post-processing technique. As by a product, optimal error estimates are acquired for potential/field and temperature in the order of $\mathcal{O}(h)$ and $\mathcal{O}(h^2),$ respectively. Finally, some numerical results are provided to confirm the theoretical analysis.
Keywords: Nonlinear thermistor equations; Galerkin mixed finite element method; Interpolation post-processing technique; Superclose and superconvergence error estimates